1975
DOI: 10.1073/pnas.72.5.1848
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of immune system by tumor cells and role of prostaglandins.

Abstract: Mice bearing syngeneic tumors, chemical and virus-induced, became immunologically unresponsive to sheep erythrocytes. The increase in the degree of unresponsiveness with tumor growth suggested a causal relationship. Immunosuppression was in fact caused by the tumor cells because the addition of tumor cells to in vitro cultures of spleen cells and sheep erythrocytes resulted in suppression of antibody response. Suppression was dose dependent with a ratio of 1 to 1000 of tumor cells to spleen cells sufficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(86 citation statements)
references
References 11 publications
2
82
0
2
Order By: Relevance
“…In our experiments when T cells were enriched (and B cells depleted) by passage over plastic bead columns, the inhibition curves of PGE~ and PGE2 on PWM approached the curves of the effects of these compounds on PHA-stimulated cells. There is some evidence in animals that PGs affect B-cell function, but there are no data in man (4,(30)(31)(32)(33). Further investigation of PG effects with other mitogens and on B-cell subpopulations may clarify this issue.…”
Section: Discussionmentioning
confidence: 92%
“…In our experiments when T cells were enriched (and B cells depleted) by passage over plastic bead columns, the inhibition curves of PGE~ and PGE2 on PWM approached the curves of the effects of these compounds on PHA-stimulated cells. There is some evidence in animals that PGs affect B-cell function, but there are no data in man (4,(30)(31)(32)(33). Further investigation of PG effects with other mitogens and on B-cell subpopulations may clarify this issue.…”
Section: Discussionmentioning
confidence: 92%
“…Prostaglandin E 2 (PGE 2 ) directly suppresses various immune cells such as macrophages, neutrophils, Th1, CTL and NK cells, while it promotes Th2, Th17 and regulatory T cell responses as well as the development of tumor-associated suppressive macrophages [93,[100][101][102][103]. The Th17-promoting activity of PGE 2 is related to its ability to suppress the production of the Th17-inhibitory IL-12, while enhancing the Th17-supporting IL-23 secretion by dendritic cells [104].…”
Section: Pgementioning
confidence: 99%
“…In line with the immunosuppressive, tumor promoting function of PGE 2 , inhibitors of prostaglandin synthesis, such as indomethacin and aspirin, have been shown to inhibit tumor growth [101] and restore anti-tumor activity by altering the balance between IL-10 and IL-12 [119]. Recently, this issue has reached a renaissance where specific COX2 inhibitors have been proposed to be potential drugs for tumor prevention [120].…”
Section: Pgementioning
confidence: 99%
“…Prostaglandins are important regulatory factors of epithelial cell function and, under certain circumstances, prostaglandins can stimulate cell proliferation and suppress immune response to neoplastic cells (Plescia et al, 1975). In addition, several groups have shown that high concentrations of free arachidonic acid can promote apoptosis, independently of prostaglandin formation (Surette et al, 1996;Chan et al, 1998;Longo et al, 1999).…”
Section: Epidemiologymentioning
confidence: 99%